Convergence of consumption patterns in the European Union - Michail, Nektarios A. (My University, 2020)
Preference homogeneity is important for both economic modelling and firm decisions. While homogeneity may be a stretched assumption and has been rejected in the existing literature, it is more useful to examine whether preferences are converging or diverging. The European Union (EU), and especially the euro area (EA) with the use of a single currency for 19 countries, are very suitable for the testing of this hypothesis. To this end, we employ 12 categories of consumption expenditure data for the 27 countries which comprise the EU to examine whether consumption patterns are converging. The results are supportive of the convergence hypothesis for the EU as a whole. However, convergence is found to be much greater in the EA countries compared to the extra-EA ones. Disaggregate results by expenditure category suggest that the hypothesis of divergence can be rejected in all, with the convergence rate being category specific. Overall, it appears that consumption patterns in the euro area appear to be converging to a common standard, at a rate approximately 50% faster than for the rest of the European Union.
Keywords: Consumption patterns; Convergence; Euro area; European Union